Inside the human genome a case for non-intelligent design - Avise, John C. (New York ; Oxford : Oxford University Press, 2010)
Humanity's physical design flaws have long been apparent (we get appendicitis and impacted wisdom teeth, for instance) but do the imperfections extend down to the molecular level of our genes? This is a comprehensive examination of why flaws empirically exist in the biological world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Molecular evolution; Human genetics; Genetic disorders